ANALISIS KERAGAMAN BENTUK TUBUH IKAN NILA STRAIN GIFT PADA TIGA TINGKATAN UMUR YANG BERBEDA - D. Ariyanto (Universitas Gadjah Mada, 2002)
A study aimed to identify morphology variability of nile tilapia (Oreochromis niloticus) strain GIFT (Genetic Improvement of Farmed Tilapia) by using standard measurement and multivariate analysis method was conducted. Elevan characters were measured at 141 fishes representing 3 levels of age (0-3 month, 3-6 month and more than 6 month) of nile tilapia strain GIFT. Multivariate analysis of variance (manova) and Pricipal Component Analysis (PCA) were applied to explore the morphological variability.The result showed that body shape of fry (0-3 month of age) was different from fishes with 3-6 month of age (consumption size), also from the broodstock. At the early level of age, development of the body shape was growth in width and length. At the consumption size and broodstock levels, the development of body shape was growth in fat too.